Effect of various warm-up devices on bat velocity of intercollegiate baseball players - Szymanski, D. J.; Beiser, E. J.; Basset, K. E.; Till, M. E.; Medlin, G. L.; Beam, J. R.; DeRenne, C. (The Journal of Strength and Conditioning Research, 2011)
A variety of warm-up devices are available to baseball players to use before their game at-bat. Past baseball research evaluating warm-up devices indicates that implements that are ±12% of standard game bat weight produce the greatest bat velocities for high school and intercollegiate players. The purpose of this study was to examine the effect of various warm-up devices on bat velocity (BV) of intercollegiate baseball players. Twenty-two Division I intercollegiate baseball players (age = 20.0 ± 1.5 years, height = 182.6 ± 8.3 cm, body mass = 91.4 ± 11.4 kg, lean body mass = 78.8 ± 8.9 kg, % body fat = 13.6 ± 3.8) participated in a warm-up with 1 of 10 weighted devices on separate days. Each of the 10 testing sessions consisted of a standardized warm-up, 3 dry swings as hard as possible with the assigned warm-up device, 2 comfortable dry swings with a standard game baseball bat followed by 3 game swings (20-second rest between swings) while hitting a baseball off of a batting tee with the same standard game baseball bat. Results indicated that there were no statistically significant differences in BV after using any of the 10 warm-up devices. For male intercollegiate baseball players, results indicate that warm-up devices varying from 623.7 to 2,721.5 g (22-96 oz.) did not change mean BV of a standard game baseball bat, suggesting that intercollegiate players can use any of the 10 warm-up devices in the on-deck circle and maintain their BV. Therefore, personal preference as to which warm-up implement to use in the on-deck circle is advised.